The application of K Phosphites to seed tubers enhanced emergence, early growth and Mycorrhizal Colonization in potato (Solanum tuberosum) - Tambascio, Cecilia (2014)
Rapid emergence and a vigorous growth prevent the seed tubers from infections by soil microbes and allow a rapid interception of solar radiation. In this work, the effect of the potassium phosphites (KPhi) applied to seed tubers of two potato cultivars on crop emergence and early growth was studied. Two experiments were performed under greenhouse and field conditions. Emergence of plants, leaf area, dry matter and the number of primary stems were measured in both experiments. Furthermore, mycorrhizal colonization was also measured on roots under field conditions. The application of KPhi reduced the period between planting and emergence, and increased leaf area and dry matter. The ratio between dry matter of aerials and underground organs was not affected by KPhi. Indigenous mycorrhizal colonization increased after KPhi application to seed tubers. These results confirm the benefit of the application of KPhi to seed tubers on early plant growth and suggest that their application in crop production would be advantageous.